3D Single Molecule Super-Resolution Microscopy of Whole Nuclear Lamina - Rozario, Ashley M.; Morey, Alison; Elliott, Cade; Russ, Brendan; Whelan, Donna R.; Turner, Stephen J.; Bell, Toby D. M. (Frontiers in Chemistry, 2022)
Single molecule (SM) super-resolution microscopies bypass the diffraction limit of conventional optical techniques and provide excellent spatial resolutions in the tens of nanometres without overly complex microscope hardware. SM imaging using optical astigmatism is an efficient strategy for visualizing subcellular features in 3D with a z-range of up to ~1 µm per acquisition. This approach however, places high demands on fluorophore brightness and photoswitching resilience meaning that imaging entire cell volumes in 3D using SM super-resolution remains challenging. Here we employ SM astigmatism together with multiplane acquisition to visualize the whole nuclear lamina of COS-7 and T cells in 3D. Nuclear lamina provides structural support to the nuclear envelope and participates in vital nuclear functions including internuclear transport, chromatin organization and gene regulation. Its position at the periphery of the nucleus provides a visible reference of the nuclear boundary and can be used to quantify the spatial distribution of intranuclear components such as histone modifications and transcription factors. We found Alexa Fluor 647, a popular photoswitchable fluorophore, remained viable for over an hour of continuous high laser power exposure, and provided sufficient brightness detectable up to 8 µm deep into a cell, allowing us to capture the entire nuclear lamina in 3D. Our approach provides sufficient super-resolution detail of nuclear lamina morphology to enable quantification of overall nuclear dimensions and local membrane features.